BILINGUAL EDUCATION AS A TOOL FOR REDUCING EDUCATIONAL INEQUALITY IN MINORITY COMMUNITIES - Sultanova Shohistaxon Shavkatovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article explores the role of bilingual education in addressing educational disparities faced by minority communities. It examines how instruction in both the mother tongue and a dominant or national language can enhance learning outcomes, strengthen cultural identity, and improve long-term academic and economic opportunities. Drawing on global case studies, the paper highlights the potential of bilingual programs to close achievement gaps, foster inclusive learning environments, and empower historically marginalized groups. It also discusses policy strategies and implementation challenges, emphasizing the need for equitable access to quality bilingual education.